A comparative study of export processing zones in the wake of sustainable development goals: Cases of Botswana, Kenya, Tanzania and Zimbabwe - Richard Adu-Gyamfi; Simplice Asongu; Tinaye S. Mmusi; Herbert Wamalwa; Madei Mangori (African Governance and Development Institute (AGDI), 2020)
The objective of this research is to assess the extent to which export processing zones in Botswana, Kenya, Tanzania, and Zimbabwe integrate the Sustainable Development Goals in their implementation and operations. We focused on four Sustainable Development Goals-gender equality, decent work, industry, and climate action. We interviewed four zone authorities, one in each country. A total of 12 firms in the agro-processing, textiles and garments, construction, and real estate sectors were also interviewed. All four zone authorities demonstrate a measure of environmental inclusiveness in their zone programmes. We found that firms in Kenya and Zimbabwe have a higher number of male than female employees, while zones in Tanzania employ more women. We propose that to promote sustainable development in these zones, policy action should concentrate on attracting firms that (are willing and able to) align with the particular Sustainable Development Goal that zone programmes are intended to achieve.
Keywords: O25; O55; O57; Q01; 330; export processing zones; sustainable development; Botswana; Kenya; SouthernAfrica; Tanzania; Zimbabwe